Essential and toxic elements in honeys consumed in Italy. Issue 21 (2nd November 2018) - Meli, Maria Assunta; Fagiolino, Ivan; Desideri, Donatella; Roselli, Carla
ABSTRACT: The aim of this study was to determine the levels of iron (Fe), manganese (Mn), chromium (Cr), copper (Cu), zinc (Zn), mercury (Hg), cadmium (Cd) and lead (Pb) in several types of honey purchased from the local consumer markets in Central Italy by Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Lead and Cd were also determined by Atomic Absorption Spectrometry with graphite tube atomization (AAS-GTA). The degree of humidity, sugar content, pH, free acidity, combined acidity (lactones) and total acidity were also measured. These elements were found to be present in honeys in various proportions depending upon (1) area foraged by bees, (2) flower type visited for the collection of nectar, and (3) quality of water in the vicinity of the hive. The honeys consumed in Italy were of good quality, but not completely free of heavy metal contamination. Compared with established recommended daily intakes, heavy metals or trace element concentrations in samples investigated, however, do not pose any serious concern to human health.